The Effect of Financial Attitude on Financial Satisfaction with Financial Management as Mediator: Empirical Evidence on Gen Z in Karawang - Fitri Novilia; Syifa Pramudita Faddila; Budi Supriatono Purnomo; Imas Purnamasari (West Science Accounting and Finance, 2023)
The Indonesian population, especially Generation Z, still faces challenges in managing their finances, both in the present and the future. This issue arises due to a lack of knowledge about financial investment. The objective of this research is to assess the financial level of Generation Z using a questionnaire filled out by 96 respondents. The independent variables involve financial attitudes, the intervention variable is financial management, and the dependent variable in this study is financial satisfaction. The data analysis technique used is descriptive analysis. The results of the descriptive analysis indicate that financial attitudes are categorized as excellent, financial management is categorized as good, and financial satisfaction is categorized as good.